2017
DOI: 10.4047/jap.2017.9.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile bond strength of repaired indirect resin composite

Abstract: PURPOSEThe objective of this study was to investigate the effect of surface treatments on microtensile bond strengths (MTBSs) of two types of indirect resin composites bonded to a conventional direct resin composite.MATERIALS AND METHODSIndirect resin composite blocks of Ceramage and SR Nexco were prepared in a plastic mold having a dimension of 10 × 10 × 4 mm. These composite blocks were divided into three groups according to their surface treatments: Group1: Sandblast (SB); Group2: Sandblast and ultrasonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 17 publications
(29 reference statements)
0
19
2
1
Order By: Relevance
“…There were no significant differences for DTS in the four composite categories. [28]. Their research showed higher DTS values compared to our study, due to the fact that composite metallic coating leads to increased material properties.…”
Section: Dts Evaluationcontrasting
confidence: 56%
“…There were no significant differences for DTS in the four composite categories. [28]. Their research showed higher DTS values compared to our study, due to the fact that composite metallic coating leads to increased material properties.…”
Section: Dts Evaluationcontrasting
confidence: 56%
“…In this study, 99% ethanol ultrasonication cleaning for 3 min was used to remove the residual alumina particles attached to the blasted surfaces of CRB and to expose fillers by partially dissolving the organic matrix, so the silanization could reach more fillers effectively. In fact, subsequent to sandblasting and ultrasonication, the nano-filler particles were exposed, which is an ideal condition to achieve silanization process effortlessly 22) .…”
Section: Discussionmentioning
confidence: 99%
“…Dental composites are a mixture of polymers and glass particles used in dental restorations to mimic the appearance and performance of teeth and are often used to repair damaged teeth [1]. Their mechanical properties have improved over the last years and consequently a lot of research has been performed to assess these properties and how they are affected by variations in particle size, polymerization depth, and viscosity [2][3][4]. In one longitudinal study it was found that out of 926 restorations investigated, 8% failed by fracture.…”
Section: Introductionmentioning
confidence: 99%